2021
DOI: 10.28982/josam.1001636
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of excision and primary closure vs. crystallized phenol treatment in pilonidal sinus disease: A comparative retrospective study

Abstract: Background/Aim: Pilonidal sinus is an inflammatory condition that affects the intergluteal sulcus. Since there is no standard treatment for pilonidal sinus, comparative studies are needed. Our study aimed to comparatively evaluate the treatment success, postoperative complications and recurrence in excision/primary repair surgery and crystallized phenol application in pilonidal sinus disease. Methods: A total of 376 pilonidal sinus patients over the age of 18 years who visited our general surgery clinic betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although some studies demonstrating higher recurrence rates after primary closure have been presented, studies supporting the primary closure method have also been published, especially in recent years. While Nihat et al [1] reported the average recurrence rate after primary closure as 3%, the recurrence rate was reported to be 7.4% in the study performed by Bulent et al [6]. These different results detected in the recurrence rates after primary closure are still a topic of discussion.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although some studies demonstrating higher recurrence rates after primary closure have been presented, studies supporting the primary closure method have also been published, especially in recent years. While Nihat et al [1] reported the average recurrence rate after primary closure as 3%, the recurrence rate was reported to be 7.4% in the study performed by Bulent et al [6]. These different results detected in the recurrence rates after primary closure are still a topic of discussion.…”
Section: Discussionmentioning
confidence: 95%
“…The diagnosis of recurrence is made with the formation of a new cyst after the penetration of the hair follicle into the subcutaneous tissue or the presence of a hair follicle in the granulation tissue after surgery. Recurrence after primary closure was reported with a rate of 0-42% in the literature [1,4,5,12]. Although some studies demonstrating higher recurrence rates after primary closure have been presented, studies supporting the primary closure method have also been published, especially in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pilonidal sinus can significantly impact people's social lives and overall comfort; severe cases may require individuals to take time off from work. Minimally invasive methods have been used to treatment the disease [1,2]. However, the prevalence of PS, its recurrence rate, and changes in skin quality in the intergluteal region due to procedures can pose challenges.…”
Section: Introductionmentioning
confidence: 99%